Sensory profiling of traditional Sorghum porridge (Aceda): advancing nutritious and culturally accepted biofortified products - Manhal Gobara Hamid; Manhal Gobara Hamid; Claudia Böhme; Khitma Abdalha Mustafa; Khitma Abdalha Mustafa; Yousif M. A. Idris; Mohammed Hamad; Faraz Muneer; Mahbubjon Rahmatov; Mohammed Elsafy; Tilal Abdelhalim (Frontiers in Sustainable Food Systems)
IntroductionMicronutrient deficiencies remain a significant public health concern in Sudan and are exacerbated by conflict and displacement.MethodsThis study assessed the sensory attributes and acceptability (hedonic scale) of Aceda, a traditional Sudanese fermented sorghum-based porridge prepared using biofortified (Dahab) and non-biofortified (Wad Ahmed and Dabar) sorghum cultivars and their blends. Sensory evaluation by 28 semi-trained assessors identified color, firmness, and mouthfeel as the key preference drivers.Results and discussionAceda made from the Dahab and Dahab + Wad Ahmed blends had the highest overall liking scores. Cluster analysis revealed two preference groups: 11 assessors favored Dahab, and 17 preferred the Dahab + Wad Ahmed blend, with age being the most influential demographic factor. Product characterization analysis showed that texture and firmness were critical for overall liking, whereas aroma and taste had a minimal impact. The sensory profiles of the Aceda products were mainly influenced by F1 (76.20%) and F2 (16.25%), accounting for 92.45% of the variance. PLS analysis identified the Dahab + Wad Ahmed blend as the most promising porridge for addressing malnutrition. STATIS analysis showed weights between 0.142 and 0.213 (mean, 0.188) and a consensus configuration range of 0.572–0.857 (mean, 0.755). These findings underscore the acceptability of biofortified sorghum porridge among consumers and highlight the role of targeted blending strategies in optimizing sensory attributes, which may support its future potential as part of broader nutritional interventions.